Incidence of Meniscal Injury and Chondral Pathology in Anterior Tibial Spine Fractures of Children. Issue 2 (March 2015) - Mitchell, Justin J.; Sjostrom, Rebecca; Mansour, Alfred A.; Irion, Bjorn; Hotchkiss, Mark; Terhune, E. Bailey; Carry, Patrick; Stewart, Jaime R.; Vidal, Armando F.; Rhodes, Jason T.
Abstract : Background: Pediatric avulsion fractures of the anterior tibial spine are injuries similar to anterior cruciate ligament injuries in adults. Sparse data exists on the association between anterior tibial spine fractures (ATSFs) and injury to the meniscus or cartilage of the knee joint in children. This research presents a retrospective review of clinical records, imaging, and operative reports to characterize the incidence of concomitant injury in cases of ATSFs in children. The purpose of this study was to better delineate the incidence of associated injuries in fractures of the anterior tibial spine in the pediatric population. Methods: We identified 58 patients who sustained an ATSF and met inclusion criteria for this study between 1996 and 2011. The subjects were separated by the Myers and McKeever classification into type I, II, and III fractures, and each of these were subclassified by associated injury pattern. Results: 59% of children with an ATSF had an associated soft tissue or other bony injury diagnosed by magnetic resonance imaging or arthroscopy. The most prevalent associated injuries were meniscal entrapment, meniscal tears, and chondral injury. We found no meniscal or chondral injury associated with type I fractures. Twenty-nine percent of type II injuries demonstrated meniscal entrapment, 33% showing meniscal tears. Seven percent demonstrated chondral injury. Forty-eight percent of type III fractures had entrapment, whereas 12% showed meniscal tears. Eight percent had a chondral injury. Conclusions: A majority (59%) of displaced ATSF had either concomitant meniscal, ligamentous, or chondral injury. This finding suggests that magnetic resonance imaging evaluation is an important aspect of the evaluation of these injuries, particularly in type II and type III patterns. To date, this study reports the largest number of patients to evaluate the specific question of concomitant injuries in ATSFs in the pediatric population. Level of Evidence: Level IV.